Managing Fund Digital Wallet Applications: Important Strategies in Financial Management - Putra, Irsan Herlandi; Rachman, Aulia (Yayasan Gema Bina Nusantara, 2024)
The goal of this research is to understand the management of digital wallet applications and identify key strategies in financial management. The research findings reveal that effective and efficient financial management heavily relies on fund management and the use of digital applications like DANA. We can conclude that fund management plays a crucial role in attaining financial objectives for individuals, businesses, and governments alike. We can manage financial resources efficiently to achieve stability and sustainable economic growth through the right strategy. Digital applications such as DANA have an important role in facilitating fund management by providing various features and services to make it easier for users to carry out daily financial transactions. The use of technology in managing funds can increase the efficiency, accessibility, and security of financial transactions. Technological innovation continues to encourage the development of better and more affordable financial services for the public.